(untitled) (Journal of Computational Mathematics, 1990)
For the problems of the left and right matrix Padé approximations, we give the necessary and sufficient conditions for the existence of their solutions. If the left Padé approximant exists, then we prove that its uniqueness is equivalent to the existence of right Padé approximants, and we further give the exact results about the dimension of the linear space ^LR^*(m,n) formed from the left Padé approximants.